2023
DOI: 10.1161/circresaha.123.323017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Vagal Nerve Activity Increases During Exercise to Enhance Coronary Blood Flow

Julia Shanks,
Mridula Pachen,
Joshua W-H. Chang
et al.

Abstract: BACKGROUND: The phrase complete vagal withdrawal is often used when discussing autonomic control of the heart during exercise. However, more recent studies have challenged this assumption. We hypothesized that cardiac vagal activity increases during exercise and maintains cardiac function via transmitters other than acetylcholine. METHODS: Chronic direct recordings of cardiac vagal nerve activity, cardiac output, coronary artery blood flow, and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recent research has found a possible mechanism to explain yoga’s benefits to the body ( 66 ). Exercise induces a four-to five-fold increase in the amount of blood pumped out by the heart, which requires faster heartbeats and more forceful contractions of heart muscles ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has found a possible mechanism to explain yoga’s benefits to the body ( 66 ). Exercise induces a four-to five-fold increase in the amount of blood pumped out by the heart, which requires faster heartbeats and more forceful contractions of heart muscles ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that the parasympathetic and sympathetic nervous systems work together in exercise to help the heart pump harder and faster. Shanks et al ( 66 ) showed that parasympathetic nerves dilate the coronary vessels by neuromodulator vasoactive intestinal peptide, allowing more blood to pump through the heart. Since yoga can improve the condition of the parasympathetic nervous system ( 69 ), it can reduce anxiety and the health condition of the entire body.…”
Section: Discussionmentioning
confidence: 99%